Microparticles from dental calculus disclose paleoenvironmental and palaeoecological records - Alessia D'Agostino; Gabriele Di Marco; Mario Federico Rolfo; Luca Alessandri; Silvia Marvelli; Roberto Braglia; Roberta Congestri; Federica Berrilli; Maria Felicita Fuciarelli; Angelica Ferracci; Antonella Canini; Angelo Gismondi (Ecology and Evolution, 2024)
Abstract Plants have always represented a key element in landscape delineation. Indeed, plant diversity, whose distribution is influenced by geographic/climatic variability, has affected both environmental and human ecology. The present contribution represents a multi‐proxy study focused on the detection of starch, pollen and non‐pollen palynomorphs in ancient dental calculus collected from pre‐historical individuals buried at La Sassa and Pila archaeological sites (Central Italy). The collected record suggested the potential use of plant taxa by the people living in Central Italy during the Copper‐Middle Bronze Age and expanded the body of evidence reported by previous palynological and palaeoecological studies. The application of a microscopic approach provided information about domesticated crops and/or gathered wild plants and inferred considerations on ancient environments, water sources, and past health and diseases. Moreover, the research supplied data to define the natural resources (e.g., C4‐plant intake) and the social use of the space during that period. Another important aspect was the finding of plant clues referable to woody habitats, characterised by broad‐leaved deciduous taxa and generally indicative of a warm‐temperate climate and grassy vegetation. Other unusual records (e.g., diatoms, brachysclereids) participated in defining the prehistoric ecological framework. Thus, this work provides an overview on the potential of the human dental calculus analysis to delineate some features of the ancient plant ecology and biodiversity.